Religion and Representation Islam and Democracy - Mattson, Ingrid; Nesbitt-Larking, Paul; Tahir, Nawaz (Cambridge Scholars Publishing, 2015)
Religion and Representation: Islam and Democracy brings together a series of reflections, studies and observations that examine the complex relationship between political representation and Islam. Through the perspectives of theology, history, sociology, philosophy and political science, contributions to this volume explore the connections between religious beliefs, religiosity, political ideals and political behaviour. Grounded in the experience of both Muslim-majority and Muslim-minority states, the chapters represent a broad cross-section of approaches that emerge from a process of exchange